The impact of privatization on efficiency and profitability1: Evidence from Chinese listed firms, 2001–2010. Issue 3 (30th March 2016) - Shi, Wendong; Sun, Jingwei
Abstract: Over the past three decades, China has undergone tremendous economic and social change as a consequence of the transition from a centrally planned to a market economy. This paper examines a key feature of this transition – the privatization of the state‐owned enterprises (SOEs) – through both a theoretical model and empirical analysis. Using newly collected primary data from a variety of sources, we study how privatization of listed SOEs affects employment, wages, profits and other aspects of economic performance at the firm level. Our major finding is that privatization results in substantial downsizing of employment, increased labour productivity and rising profitability.